Sentinel node detection in early breast cancer with intraoperative portable gamma camera: UK experience. (April 2017) - Ghosh, Debashis; Michalopoulos, Nikolaos V.; Davidson, Timothy; Wickham, Fred; Williams, Norman R.; Keshtgar, Mohammed R.
Abstract: Purpose: Access to nuclear medicine department for sentinel node imaging remains an issue in number of hospitals in the UK and many parts of the world. Sentinella ® is a portable imaging camera used intra-operatively to produce real time visual localisation of sentinel lymph nodes. Methods: Sentinella ® was tested in a controlled laboratory environment at our centre and we report our experience on the first use of this technology from UK. Moreover, preoperative scintigrams of the axilla were obtained in 144 patients undergoing sentinel node biopsy using conventional gamma camera. Sentinella ® scans were done intra-operatively to correlate with the pre-operative scintigram and to determine presence of any residual hot node after the axilla was deemed to be clear based on the silence of the hand held gamma probe. Results: Sentinella ® detected significantly more nodes compared with CGC (p < 0.0001). Sentinella ® picked up extra nodes in 5/144 cases after the axilla was found silent using hand held gamma probe. In 2/144 cases, extra nodes detected by Sentinella ® confirmed presence of tumour cells that led to a complete axillary clearance. Conclusions: Sentinella ® is a reliable technique for intra-operative localisation of radioactive nodes. It provides increased nodal visualisation rates compared to static scintigram imaging and proves to be an important tool for harvesting all hot sentinel nodes. This portable gamma camera can definitely replace the use of conventional lymphoscintigrams saving time and money both for patients and the health system. Highlights: Sentinella ® is a reliable tool for intraoperative localisation of radioactive nodes. Sentinella ® detected significantly more nodes than the conventional gamma camera. This portable gamma camera can replace the use of conventional lymphoscintigrams.